Evaluation of efficacy of topical propranolol - Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
Case 1. A 3-month-old child presented with superficial, just infiltrated, red hemangioma with numerous proliferative peripheral buttons on the abdomen (Fig. 1). We decided to treat only the right half of the lesion with topical 1% propranolol, 2 times a day, to evaluate the effectiveness of the drug. After 30 days the right half showed a greater extension of the gray patches and a decrease of the peripheral infiltrative buttons (Fig. 2), leading us to extend the therapy to the whole lesion. Case 2. A 1-month-old child presented with superficial hemangioma of the left side characterized by numerous proliferative buttons (Fig. 3). We started treatment with topical 1% propranolol, 2 times a day, only on the lower half of hemangioma. After one month the proliferative buttons were less evident on the treated area, leading us to extend the topical treatment with 1% propranolol to the whole lesion.